Marketing Strategy For Gold Installment Products in Increasing Customer Interest at Bank Syariah Indonesia: A Systematic Literature Review (2022-2026) - Lutfiya Ardania; Dunuroi Assuryani; Achmad Junaidi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Global gold price volatility and high inflation during the 2022–2026 period established gold as a primary safe-haven asset, prompting Bank Syariah Indonesia (BSI) to expand its